New Trident Molecule with Phosphoric Acid Functionality for Trivalent Rare Earth Extraction - Keisuke Ohto; Hiromasa Murashima; Hiroshi Murakami; Shintaro Morisada; Hidetaka Kawakita; Marco Wenzel; Jan J. Weigand; Karsten Gloe (Indonesian Journal of Chemistry, 2017)
Tripodal extraction reagent with three phosphoric acid groups, together with the corresponding monopodal molecule has been prepared to investigate some metals extraction behavior, in particular, trivalent rare earth elements (REEs). The tripodal reagent exhibited extremely high selectivity for metals with high valency such as Zr(IV), In(III), Lu(III), and Fe(III). Tripodal reagent also exhibited exceptionally high extraction ability compared with the corresponding monopodal one in the extraction of trivalent rare earths. The result for the stoichiometry of tripodal reagent to heavy rare earths showed the inflection point between Er (2:1 for a ligand with ion) and Tm (1:1). The extraction reactions were determined for all rare earths with both reagents. The extraction equilibrium constants (Kex), the separation factors (β), half pH values (pH1/2), difference half pH values (ΔpH1/2) for extraction of REEs with both reagents are estimated.